The Role Of Parents In Guiding Children In The Field Of Tahfidz Al-Qur'an On Jalan Paseh Lukmanul Hakim Gang H Patonah: - Yuliandini, Adela; Suryana, Dudung; Nugraha, Fajar (CV. Generasi Insan Rafflesia, 2025)
Inggris This study aims to analyze the role of parents in guiding children to achieve Al-Qur'an memorization achievements on Jalan Paseh Lukmanul Hakim Gang H. Patonah, Tasikmalaya. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The subjects of the study included parents, children who memorized the Al-Qur'an, and tahfidz teachers at local madrasahs. The results of the study showed that parents play a multidimensional role as role models, motivators, guides, facilitators, and managers in the process of children's tahfidz. The strategies applied include role models, giving rewards, mentoring with the talaqqi method, and managing time and a conducive environment. Obstacles such as gadget distractions and boredom were successfully overcome with creative solutions, such as limiting play time and a flexible approach. Collaboration between parents and tahfidz institutions is also a supporting factor for success. This study concludes that the active role of parents, even with limited time and resources, is able to create an optimal environment for children to achieve Al-Qur'an memorization achievements. These findings provide practical implications for parents and educators in developing effective tahfidz learning strategies.